CONTRASTIVE ANALYSIS OF PHRASEOLOGICAL UNITS WITH THE CONCEPT SOMATIC IN ENGLISH AND UZBEK LANGUAGES (International Conference on Economics, Finance, Banking and Management, 2025)
This article examines phraseological units with the concept “somatic” terms related to body parts in English and Uzbek languages. The study investigates the semantic, cultural, and linguistic features of somatic phraseological units, shedding light on similarities and differences between the two languages. By exploring these units through a contrastive lens, this work contributes to understanding how cultural and linguistic identities are reflected in phraseology.